SISTEM PEMANEN AIR HUJAN SEBAGAI STRATEGI ADAPTASI DAN MITIGASI PERUBAHAN IKLIM DI KELURAHAN SUKAGALIH GARUT - Azzahra, Ahsanti; Farohi Arinalhaq Mubarok, Mochammad; Walfitra, Ilham; Zidan Utama, Muhamad; Firdaus, M. Rizki; Nurpassah, Faisal; Febriana Putri, Shalma; Iskandar, Muhammad; Saprika, Shinta; Perwito, Perwito (ABISATYA DINAMIKA ISWARA PUBLISHING, 2024)
Anticipating the negative effects of climate change and taking appropriate actions to prevent or minimize damage or take advantage of opportunities that may arise is called adaptation. Mitigation is intended to reduce the impact of climate change through preventing or reducing greenhouse gas (GHG) emissions into the atmosphere. In Indonesia, the phenomenon of climate change is a big problem for the environment. Almost all areas of Indonesia are vulnerable to natural disasters. The threat of climate anomalies includes floods, landslides, fires, scarcity of water resources, and crop failure due to drought. In response to this, the Regular Group 63 KKN Muhammadiyah University of Bandung (UMB) brought forward an innovation in the use of rainwater which aims to be a form of adaptation and mitigation to climate change. This program is implemented on a small scale at the RW level, namely for the RW community in Perum Griya Surya Indah (GSI), Sukagalih Village, Tarogong Kidul District, Garut Regency. This rainwater harvester can be a sustainable solution for the community as another source of water used for daily needs.